1951
DOI: 10.1113/jphysiol.1951.sp004541
|View full text |Cite
|
Sign up to set email alerts
|

The heat production associated with the maintenance of a prolonged contraction and the extra heat produced during large shortening

Abstract: In a recent paper (Hill, 1949 a), it was shown that the heat produced in a single twitch is made up of two parts: (a) the heat of shortening which is simultaneous with and proportional to the shortening, and (b) the heat of activation. The latter starts at its maximum speed shortly after a shock, falling in rate from then on and finishing by the time that relaxation begins. In another paper (Hill, 1949c) the use of a quick stretch applied shortly after a shock showed that the full strength of a contraction (eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

1971
1971
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 6 publications
4
44
0
Order By: Relevance
“…The time taken for the tension to fall by 20 % from its maximum, TO-2R, is variable. Abbott (1951) has shown that the change with time of heat rate during an isometric tetanus of twitch fibres K. FLOYD AND I. C. H. SMITH is accompanied by changes in tension relaxation rate. This may be because both parameters measure the rate of cross-bridge turnover.…”
Section: Isometric Experimentsmentioning
confidence: 99%
“…The time taken for the tension to fall by 20 % from its maximum, TO-2R, is variable. Abbott (1951) has shown that the change with time of heat rate during an isometric tetanus of twitch fibres K. FLOYD AND I. C. H. SMITH is accompanied by changes in tension relaxation rate. This may be because both parameters measure the rate of cross-bridge turnover.…”
Section: Isometric Experimentsmentioning
confidence: 99%
“…During prolonged repetitive stimulation [Kt] will increase to a steady-state value which should be attained more rapidly, the higher the frequency of stimulation. Abbott (1951) found that Q decreased to a steady value more rapidly at a higher frequency; the steady value was slightly affected by the increase in frequency.…”
Section: Discussionmentioning
confidence: 90%
“…The rate constant for relaxation, r, depends on the duration of stimulation during the tetanus, D, as well as on L and T. The results of Abbott (1951) and Aubert (1956) and F, = 10.6 kcal/mole. The data were not sufficient in number or precision to estimate 4)(s, T), although clearly increased with temperature at all sarcomere lengths.…”
Section: Characteristics Of Rmentioning
confidence: 87%
See 2 more Smart Citations